SUMOylation by a Stress-Specific Small Ubiquitin-Like Modifier E2 Conjugase Is Essential for Survival of Chlamydomonas reinhardtii under Stress Conditions - Knobbe, Amy R. (Plant Physiol, 2015)
Posttranslational modification of proteins by small ubiquitin-like modifier (SUMO) is required for survival of virtually all eukaryotic organisms. Attachment of SUMO to target proteins is catalyzed by SUMO E2 conjugase. All haploid or diploid eukaryotes studied to date possess a single indispensable SUMO conjugase. We report here the unanticipated isolation of a Chlamydomonas reinhardtii (mutant5 [mut5]). in which the previously identified SUMO conjugase gene C. reinhardtii ubiquitin-conjugating enzyme9 (CrUBC9) is deleted. This surprising mutant is viable and unexpectedly, displays a pattern of protein SUMOylation at 25°C that is essentially identical to wild-type cells. However, unlike wild-type cells, mut5 fails to SUMOylate a large set of proteins in response to multiple stress conditions, a failure that results in a markedly reduced tolerance or complete lack of tolerance to these stresses. Restoration of expected stress-induced protein SUMOylation patterns as well as normal stress tolerance phenotypes in mut5 cells complemented with a CrUBC9 gene shows that CrUBC9 is an authentic SUMO conjugase and, more importantly, that SUMOylation is essential for cell survival under stress conditions. The presence of bona fide SUMOylated proteins in the mut5 mutant at 25°C can only be explained by the presence of at least one additional SUMO conjugase in C. reinhardtii, a conjugase tentatively identified as CrUBC3. Together, these results suggest that, unlike all other nonpolyploid eukaryotes, there are at least two distinct and functional SUMO E2 conjugases in C. reinhardtii, with a clear division of labor between the two sets: One (CrUBC9) is involved in essential stress-induced SUMOylations, and one (CrUBC3) is involved in housekeeping SUMOylations.